Supranutritional dietary selenium depressed expression of selenoprotein genes in three immune organs of broilers. (21st June 2016) - Tang, Jiayong; Huang, Xiaofeng; Wang, Longqiong; Li, Qiang; Xu, Jinyang; Jia, Gang; Liu, Guangmang; Chen, Xiaoling; Shang, Haiying; Zhao, Hua
Abstract: The objective of this study was to investigate the effects of supranutritional dietary selenium (Se) on selenoproteins expression in three immune organs of chickens. A total of 160 1‐day‐old male Cobb broilers were randomly divided into two groups and fed a Se‐deficient corn‐soybean basal diet supplemented with 0.3 (adequate) and 3.0 (excess) mg/kg Se for 42 days. Immune organs were collected, and effects of supranutritional Se on messenger RNA abundance of 23 selenoprotein genes and eight inflammation‐related genes were compared at day 42. Also enzyme activities were measured at days 14, 28 and 42. The results showed supranutritional dietary Se depressed growth performance of chicken and down‐regulated nine and three selenoprotein genes in thymus and spleen, respectively, and only Sepp1 was up‐regulated in the bursa of Fabricius. Also three, three and seven inflammation‐related genes were up‐regulated in three organs, respectively. Supranutritional Se elevated ( P  < 0.05) activities of superoxidase dismutase, total antioxidant capacity and glutathione peroxidase, mainly in early stages. In summary, supranutritional Se resulted in down‐regulation of selenoprotein genes and up‐regulation of inflammation‐related genes in three immune organs of chicken, which indicated potential roles of those selenoprotein genes in immune organs of the chicken.